ANALISIS KEBUTUHAN SDM DAN SARANA PRASARANA SEKOLAH JENJANG PENDIDIKAN DASAR DAN MENENGAH PERTAMA DI KOTA PANGKALPINANG - Nurwasya; Marlina Safitri; Nurjanah; Vika Martahayu (UNMUHBABEL Press, 2025)
This study aims to analyze the suitability and fulfillment of infrastructure and human resource needs at the elementary and junior high school levels in Pangkalpinang City as a basis for regional education policy planning. The study used a qualitative approach with descriptive analytical methods. Data were collected through observation, surveys, structured interviews, and documentation. Data validity was ensured through triangulation of techniques and sources to verify findings in the field. The results showed that the condition of elementary and junior high school classrooms varied from decent to severely damaged. The needs analysis revealed the urgency of rehabilitation for classrooms with moderate to severe damage and the need to standardize supporting facilities such as lighting, prayer rooms, health facilities, and counseling rooms, which currently do not meet ideal criteria. In terms of human resources, an equitable distribution of teaching staff was identified to address the disparity in academic background and employment status, although teacher competency was generally categorized as good to excellent. The study concluded that fulfilling the gap between actual conditions and standard facility needs and the redistribution of human resources must be a top priority to improve the quality of education services in Pangkalpinang City.